LAW ENFORCEMENT AGAINST CRIMINAL ACTORS OF CHILD PORNOGRAPHY THROUGH SOCIAL MEDIA - Dwi Nur Fauziah Ahmad; Latifatul Hidayati (Jurnal Hukum Replik, 2021)
This study discusses the crime of child pornography through social media. This research uses empirical and normative legal research where empirical legal research carried out by collecting data through observation, interviews. Sources of data used by researchers in this study are primary data sources compiled from observations, interviews and questionnaires in the field and secondary data sources collected from library research. This research analyzed using descriptive qualitative methods. In this research, the theory used is the Law Enforcement Theory according to Joseph Goldstein, namely: Total Enforcement, meaning the scope of criminal law enforcement as formulated by substantive criminal law. This research expected to give advice, recommendations and study material about cases of child pornography in the community Key words: pornography; Law, Children, Social Media